1998
DOI: 10.1136/adc.78.5.474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormone on height, weight, and body composition in Prader-Willi syndrome

Abstract: Aims-To evaluate the eVect of the administration of growth hormone on stature, body weight, and body composition in children aged between 4 and 10 years with Prader-Willi syndrome. Methods-Height, weight, and skinfold thickness were recorded in 25 children using standard anthropometric techniques at recruitment, and six months later, shortly before the start of daily subcutaneous injections of growth hormone. Body composition was assessed via a measurement of total body water using stable isotopes. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 12 publications
0
22
1
5
Order By: Relevance
“…36,37 In adults, GHD is associated with shrinking of the ICW compartment, possibly as a result of protein catabolism. 10,38 The higher ECW/ICW ratio in the group with PWS seems to support the hypothesis of functional GHD.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 In adults, GHD is associated with shrinking of the ICW compartment, possibly as a result of protein catabolism. 10,38 The higher ECW/ICW ratio in the group with PWS seems to support the hypothesis of functional GHD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that in PWS patients GH treatment (GHT) reduces fat mass and increases body free fat mass percentage [4,12,13,14], improves respiratory muscle strength and endurance [15], and increases resting metabolic rate as well as physical strength and agility[14]. Changes in behaviour have also been observed [16] and beneficial effects on growth velocity have been demonstrated in many studies [6,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…O tratamento destes pacientes com rhGH pode melhorar a estatura final, porém a grande contribuição do GH tem sido a melhora da composição corpórea, minimizando as conseqüências clínicas desta síndrome (28)(29)(30). Em nossos pacientes, observamos aumento da velocidade de crescimento, principalmente no primeiro ano de tratamento, porém acompanhado de um avanço proporcional na idade óssea.…”
Section: Discussionunclassified
“…Os resultados sugerem que o tratamento propicia efeitos benéficos na aparência físi-ca, energia e resistência, melhorando assim a inserção psicossocial das crianças afetadas (16,29,40). Muitas destas observações foram relatadas espontaneamente pelos pais.…”
Section: Discussionunclassified